2019
DOI: 10.1101/658229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Caenorhabditis elegansExhibits Positive Gravitaxis

Abstract: 10Whether or not the micro swimmer Caenorhabditis elegans senses and respond to gravity is 11 unknown. We find that C. elegans aligns its swimming direction with that of the gravity vector 12 (positive gravitaxis). When placed in an aqueous solution that is denser than the animals, they 13 still orient downwards, indicating that non-uniform mass distribution and/or hydrodynamic 14 effects are not responsible for animal's downward orientation. Paralyzed worms and worms 15 with globally disrupted sensory cilia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Our findings that C. elegans dauer larvae exhibit pronounced negative gravitaxis contrasts with prior studies which found no gravitactic behavior in dauers, or that reported positive reorientation toward the gravitational vector in adults 16,17 . These differences are likely attributable to several parameters of assay design.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings that C. elegans dauer larvae exhibit pronounced negative gravitaxis contrasts with prior studies which found no gravitactic behavior in dauers, or that reported positive reorientation toward the gravitational vector in adults 16,17 . These differences are likely attributable to several parameters of assay design.…”
Section: Resultscontrasting
confidence: 99%
“…In previous studies, C. elegans dauer larvae showed no gravitactic preference, in contrast with C. japonica , which negatively gravitax on vertically oriented Petri plates 16 . Other studies reported that C. elegans adults show a tendency to orient downwards when swimming in liquid, suggesting potential positive gravitaxis 17 . However, as in Drosophila and the ascidian Ciona , the ability of nematodes to undergo gravitaxis is likely context-dependent 18,19 .…”
Section: Introductionmentioning
confidence: 95%
“…At present, the only comprehensive synaptic connectivity maps (i.e., connectomes) are from two invertebrates: the adult nematode Caenorhabditis elegans [20] and a larva of the tunicate Ciona intestinalis [21]. Although there are conflicting reports on whether C. elegans has a gravity response [18,22], Ciona larvae clearly do. The most commonly described gravitactic behavior in Ciona larvae is negative gravitaxis [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its simplicity, recent studies reveal that C. elegans can detect more of this universe than previously thought. It is even possible that worms can detect gravitational forces (Chen, Ko, Chuang, Bau, & Raizen, 2019). We invite the reader to ponder what else this amazing creature can do!…”
Section: Discussionmentioning
confidence: 98%